Maternal treatment with dexamethasone during gestation alters sexual development markers in the F1 and F2 male offspring of Wistar rats. (31st August 2016) - Jeje, S. O.; Raji, Y.
Abstract : Maternal treatment with dexamethasone (Dex) in threatening preterm delivery alters activities at the hypothalamic–pituitary–adrenal axis in the offspring. This alteration may interfere with reproductive function. The impact of gestational Dex exposure on male reproductive function of the offspring was investigated. A total of 25 pregnant rats randomly assigned to five groups ( n =5) were treated with normal saline (control), Dex (100 μg/kg/day sc) during gestation days (GD) 1–7, 8–14, 15–21 and 1–21, respectively. Birth weight, anogenital distance (AGD), pubertal age, sperm parameters, hormonal profile and histopathology of testis and epididymis were determined in the F1 and F2 offspring. Results showed a significant increase ( P <0.05) in pubertal age, serum corticosterone and gonadotropin-releasing hormone (GnRH) levels in the male offspring of DexGD 15–21 and 1–21 groups and a significant decrease ( P <0.05) in serum testosterone, luteinizing hormone, birth weight and AGD at birth in the male F1 offspring. In the F2 offspring, there was a significant reduction ( P <0.05) in serum corticosterone, testosterone, follicle-stimulating hormone and GnRH when compared with the control. Dex treatment at GD 15–21 and 1–21 significantly reduced ( P <0.05) sperm motility and normal morphology in the F1 and F2 offspring. Maternal Dex treatment in rats during late gestation may disrupt sexual development markers in the F1 and F2 male offspring.